2006
DOI: 10.1021/np060166z
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Activity and Chemical Constituents of Eysenhardtia platycarpa

Abstract: The methanolic extracts from branches (BEP) and leaves (LEP) of Eysenhardtia platycarpa significantly decreased the blood glucose levels in normal and streptozotocin (STZ)-induced diabetic rats. One new flavone, (1"R)-5,4',1"-trihydroxy-6,7-(3",3"-dimethylchroman)flavone (1), together with the known compounds 5,7-dihydroxy-6-methyl-8-prenylflavanone (3), 5,7-dihydroxy-8-methyl-6-prenylflavanone (4), 5,7-dihydroxy-6-prenylflavanone (5), 5,7-dihydroxy-8-prenylflavanone (6), 3-O-acetyloleanolic acid (7), oleanoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 36 publications
2
47
0
1
Order By: Relevance
“…Lupeol has been reported to exhibit anti-diabetic activity in in vitro and in vivo models (Ali et al, 2006;Narvaez-Mastache et al, 2006;OrtizAndrade et al, 2007;Na et al, 2009). Several studies showed that lupeol exhibits antihyperglycemic activity and its administration lowers the risk of development of diabetes in animal models (Ali et al, 2006;Narvaez-Mastache et al, 2006Ortiz-Andrade et al, 2007Na et al, 2009).…”
Section: Lupeol As Anti-diabetic Agentmentioning
confidence: 99%
“…Lupeol has been reported to exhibit anti-diabetic activity in in vitro and in vivo models (Ali et al, 2006;Narvaez-Mastache et al, 2006;OrtizAndrade et al, 2007;Na et al, 2009). Several studies showed that lupeol exhibits antihyperglycemic activity and its administration lowers the risk of development of diabetes in animal models (Ali et al, 2006;Narvaez-Mastache et al, 2006Ortiz-Andrade et al, 2007Na et al, 2009).…”
Section: Lupeol As Anti-diabetic Agentmentioning
confidence: 99%
“…oral) in STZ-induced diabetic rats. 14) Likewise, Shaiq et al 36) demonstrated that oleanolic acid and some of its derivatives inhibit a-glucosidase; therefore, the hypoglycemic effect of 6 and 1 could be due to this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…12) Previous studies on Eysenhardtia species have highlighted the hypoglycemic activity of E. polystachya 13) and the antihyperglycemic activity of E. platycarpa, 14) as well as the isolation of cytotoxic flavonoids 15,16) and 3-O-acetyloleanolic acid [which displayed antihyperglycemic activity in streptozotocin (STZ)-induced diabetic rats 14) ]. As part of our screening of plants for the isolation of substances with antioxidant and antihyperglycemic potential, 14,17) this study was conducted to A) assess the antioxidant effects of extracts from E. platycarpa, E. punctata, and E. subcoriacea, as well as of compounds 1-8, natural constituents isolated from E. platycarpa (Chart 1), in a rat pancreas model and in a 1,1 diphenyl-2-picrylhydrazyl (DPPH) radical scavenger assay; B) synthesize 1, which displayed a protective effect against 2,2-azo-bis(2-amidinopropane)dihydrochloride (AAPH)-induced damage in pancreatic homogenate; and C) evaluate the protective effect of 1 in STZinduced diabetic rats.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations